Assessment of the agronomic value of solar-dried sludge and heavy metals bioavailability based on the bioaccumulation factor and translocation index - An-nori, Amal; El Mejahed, Khalil; Fels, Loubna El; Touhami, Driss; Ezzariai, Amine; El Gharous, Mohamed; Hafidi, Mohamed (Frontiers in Environmental Science, 2023)
This study aimed to assess the agronomic value of solar-dried sludge (SDS) and the transfer of Cr, Ni, Pb, and Cu to wheat (Triticum aestivum) and faba bean (Vicia faba). A greenhouse experiment was performed involving two rates of SDS (15 t/ha and 30 t/ha) from an activated sludge-based wastewater treatment plant. In addition to the single use of an SDS amendment, co-application of SDS and mineral fertilizers was also included to determine the best scenario resulting in high yields and less negative implications on the environment. Data for both wheat and faba bean showed that applying SDS at 30 t/ha led to competitive yields compared to the ones obtained previously, while 15 t/ha of SDS and mineral fertilizers were co-applied. The use of SDS increased soil organic matter, slightly decreased the pH value, and increased soil salinity. The contents of Ni, Cu, and Pb were not significantly affected by the application of SDS. Only Cr showed high soil concentrations in proportion to the increasing rates of SDS. The bioaccumulation of heavy metals in roots was more important in 30 t/ha than that in 15 t/ha amended soil. In the case of wheat, the bioconcentration factor (BCF) root values correspond to the following order: Cr (0.89) >Cu (0.85)> Ni (0.28)> Pb (0.22). In the case of faba bean, BCF roots were observed as follows: Cu (1.04 > Ni (0.37)> Cr (0.16)> Pb (0.15). Wheat excluded Cr, Ni, and Pb from the uptake by shoots, and Cu was translocated from roots to shoots with a percentage of 11% at 30 t/ha of applied SDS. Faba beans demonstrated more important values of HM’s translocation by respecting this order (Ni (37.7%) > cu (30.24%)> Cr (17.59%), while Pb was excluded from the translocation. No significant difference was observed regarding the translocation index when the sludge rate has been duplicated from 15 t/ha to 30 t/ha. Based on these outcomes, SDS used at the rate of 30 t/ha is the best scenario to amend the soil and provide nutrients to plants. Wheat is translocating less heavy metal to the edible part; it is, thus, the most suitable crop to be involved in the current context.